Economic Growth, Renewable Energy and Methane Emissions: Is there an Enviromental Kuznets Curve in Austria? - Benavides, Mayra; Ovalle, Kevin; Torres, Carolina; Vinces, Tatiana (International Journal of Energy Economics and Policy, 2017)
This paper provides empirical evidence of Environmental Kuznets Curve for Austria. Using the Autoregressive Distributed Lag (ARDL) method, the relationship between methane emissions (CH4), Gross Domestic Product (GDP), electricity production from renewable energy sources (excluding hydro) and trade openness is analyzed; the variables are used in per capita terms except for trade openness. In the long term, co-integration analysis indicates that the variables have a distribution inverted U-shaped and Granger causality test shows unidirectional causality between CH4 and the variables involved. Since CH4 is the second highest Greenhouse Gas (GHG) emitted in the world, political and academic implications of this study are relevant to include in planning decisions that aim to mitigate climate change. Keywords: Methane emissions, Renewable Energy, Trade Openness. JEL Classifications: C32, O52, Q43, Q54